Estimating the effect of tracking tag weight on insect movement using video analysis: A case study with a flightless orthopteran - Kaláb, Oto; Musiolek, David; Rusnok, Pavel; Hurtik, Petr; Tomis, Martin; Kočárek, Petr (PloS one, 2021)
In this study, we describe an inexpensive and rapid method of using video analysis and identity tracking to measure the effects of tag weight on insect movement. In a laboratory experiment, we assessed the tag weight and associated context-dependent effects on movement, choosing temperature as a factor known to affect insect movement and behavior. We recorded the movements of groups of flightless adult crickets Gryllus locorojo (Orthoptera:Gryllidae) as affected by no tag (control); by light, medium, or heavy tags (198.7, 549.2, and 758.6 mg, respectively); and by low, intermediate, or high temperatures (19.5, 24.0, and 28.3°C, respectively). Each individual in each group was weighed before recording and was recorded for 3 consecutive days. The mean (± SD) tag mass expressed as a percentage of body mass before the first recording was 26.8 ± 3.7% with light tags, 72 ± 11.2% with medium tags, and 101.9 ± 13.5% with heavy tags. We found that the influence of tag weight strongly depended on temperature, and that the negative effects on movement generally increased with tag weight. At the low temperature, nearly all movement properties were negatively influenced. At the intermediate and high temperatures, the light and medium tags did not affect any of the movement properties. The continuous 3-day tag load reduced the average movement speed only for crickets with heavy tags. Based on our results, we recommend that researchers consider or investigate the possible effects of tags before conducting any experiment with tags in order to avoid obtaining biased results.
Keywords: telemetrie; Animals; Movement; pohyb; teplota; Linear Models; Rest; odpočinek; Flight, Animal; lineární modely; Video Recording; Temperature; tělesná hmotnost; let zvířat; Telemetry; Body Weight; audiovizuální záznam; zvířata; Gryllidae